1983
DOI: 10.1164/arrd.1983.127.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Air-Space Immunoglobulin Production and Levels in Bronchoalveolar Lavage Fluid of Normal Subjects and Patients with Sarcoidosis1–4

Abstract: The purpose of this study was to examine the relationship between immunoglobulin production and immunoglobulin levels in bronchoalveolar lavage (BAL) fluid and serum of normal subjects and patients with sarcoidosis. Eleven normal volunteers and 17 patients were studied. In normal subjects, no important relationship existed between the number of immunoglobulin-secreting cells and immunoglobulin levels in BAL or serum. By contrast, in patients with sarcoidosis, a highly significant correlation existed between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…High IgG/albumin ratio and increased numbers of IgG secreting cells has been documented in BAL fluid from sarcoidosis patients, suggesting that immunoglobulins are produced locally [21,[31][32][33][34]. VALEYRE et al [29] found a negative correlation between BAL IgG/ albumin but not IgA/albumin ratio and TLCO corrected for alveolar volume in patients with sarcoidosis of recent origin (radiographic Stages 1, 2 and 3, mean disease duration of 12.5 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High IgG/albumin ratio and increased numbers of IgG secreting cells has been documented in BAL fluid from sarcoidosis patients, suggesting that immunoglobulins are produced locally [21,[31][32][33][34]. VALEYRE et al [29] found a negative correlation between BAL IgG/ albumin but not IgA/albumin ratio and TLCO corrected for alveolar volume in patients with sarcoidosis of recent origin (radiographic Stages 1, 2 and 3, mean disease duration of 12.5 months).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that immune process could be predominantly associated with TLCO impairment in early stages of the disease. However, it remains unclear whether BAL immunoglobulins represent only markers of immunological events or play a direct role in the pathogenesis of alveolocapillary derangement [31][32][33]. Circulating immune complexes have been described in acute sarcoidosis [1], and it has recently been suggested that immunoglobulins, in particular IgA and IgG, could directly interact with alveolar macrophages [36].…”
Section: Discussionmentioning
confidence: 99%
“…The first is an increase in the transudation of protein from the blood, presumably because of inflammation within the lung. This conclusion is based on the observation that albumin concentrations in lavage fluid are also frequently increased in sarcoidosis, "1 12 37 The increased immunoglobulin concentrations in lung secretions from patients with interstitial lung disease clearly result mainly from local synthesis by plasma cells and, by contrast with the normal lung, a considerable proportion of this protein is derived from cells lining the airways. The source of these cells is not known.…”
Section: Interstitial Lung Diseasesmentioning
confidence: 99%
“…In normal subjects and in patients with various lung diseases, some local immunoglobulin production has been demonstrated in the lung. This is probably derived from plasma cells contained in the bronchial lamina propria or from cells in the airway lumens [31].…”
Section: Discussionmentioning
confidence: 99%